Factors Related to Malaria in Pregnant Women in the Work Area of Kambaniru Health Center East Sumba District - Johana B Atameha; Margaretha Malo (JURNAL KESEHATAN PRIMER, 2018)
Background: This disease is one of the major health problems in NTT province. Where the disease is still the cause of death for infants, toddlers and pregnant women.Nearly 90% of villages in NTT province make up almost 100% of malaria endemic villages. Pregnant women in malaria endemic areas have a high risk,because the impact of malaria will cause anemia and malaria treatment will affect the growth and development of the fetus it contains,the worst can also cause pain and death and fetus. Methods: This research metode is analytic observational research with cross sectional study design approach.The study was conducted from September to October 2017 in pregnant women in the working area of Puskesmas Kambaniru.The sampling technique used was random samplimg,66 samples of total population of 198 pregnant women.The instrument used in this study is a questionnaire. Results: The result of the research will be analyzed by univariate and bivariate analysis by using linear regression.The result of this research can be knowledge (0.017) and attitude (0.001).While the external factors of the incidence of malaria in pregnant women are related variable health care facilities (0.018).